Protein-Labs on Separative Analytical Scale in Medicinal Chemistry: from the Proof of Concept to Applications - Temporini, Caterina; Calleri, Enrica; Brusotti, Gloria; Massolini, Gabriella (Current Organic Chemistry, 2016)
Coupling of a macromolecule such as an enzyme or a receptor to a chromatographic support has revealed a powerful analytical tool to face different aspects related to drug discovery. Chromatographic systems with immobilized macromolecules have been developed to be used for different applications in pharmaceutical analysis including enzyme inhibitor screening, biopharmaceutics structural analysis, chiral separations and binding studies. These areas of research are very challenging both for the technological and for the applicative aspects. This review offers an overview of general strategies and references that can be considered in order to develop innovative and reliable “protein-labs” for specific separative analytical applications of pharmaceutical interest.
Keywords: Protein immobilization